2017
DOI: 10.1103/physrevb.96.024407
|View full text |Cite
|
Sign up to set email alerts
|

Coupled-mode theory for the interaction between acoustic waves and spin waves in magnonic-phononic crystals: Propagating magnetoelastic waves

Abstract: We have investigated co-directional and contra-directional couplings between spin wave and acoustic wave in one-dimensional periodic structure (magphonic crystal). The system consists of two ferromagnetic layers alternating in space. We have taken into consideration materials commonly used in magnonics: yttrium iron garnet, CoFeB, permalloy, and cobalt. The coupled mode theory (CMT) formalism have been successfully implemented to describe magnetoelastic interaction as a periodic perturbation in the magphonic c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…The possibility of miniaturization of spin-wave-based logic devices is dependent on the wavelength, thus the attention is focused on searching the ways of generation of short SWs. Several approaches has been recently reported: shortening the wavelength in a tapered waveguide [9], microwave-to-SW transducers based either on magnetic wires [10], nanostructure edges [11], diffraction gratings [12][13][14], coplanar waveguides [15] or anisotropy-modulated multiferroic heterostructures [16], transduction of acoustic waves into short SWs due to magneto-elastic coupling [17,18], and emitters based on current-driven oscillating pinned domain walls [19].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of miniaturization of spin-wave-based logic devices is dependent on the wavelength, thus the attention is focused on searching the ways of generation of short SWs. Several approaches has been recently reported: shortening the wavelength in a tapered waveguide [9], microwave-to-SW transducers based either on magnetic wires [10], nanostructure edges [11], diffraction gratings [12][13][14], coplanar waveguides [15] or anisotropy-modulated multiferroic heterostructures [16], transduction of acoustic waves into short SWs due to magneto-elastic coupling [17,18], and emitters based on current-driven oscillating pinned domain walls [19].…”
Section: Introductionmentioning
confidence: 99%
“…In an analytical approach, the dispersion relation is compared to the expected linear dependence for an elastic shear wave. For this the velocity of sound c was calculated using where G CoFeB = 70 GPa is the shear modulus of CoFeB 33 . With the volumetric mass density 33 ρ CoFeB = 7050 kg/m 3 , a shear wave propagation velocity of c = 3.151 km/s is calculated.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the numerical gradient evaluation, the force input was reduced by one cell along the z -direction compared to the micromagnetically simulated magnetisation distribution. For the calculation the following isotropic material parameters were used a Young’s modulus of E CoFeB = 182 GPa, a Poisson’s ratio of ν CoFeB = 0.3, and a density of ρ CoFeB = 7050 kg/m 3 33 , and respectively E glass = 82 GPa, ν glass = 0.206, and ρ glass = 2510 kg/m 3 40 .…”
Section: Methodsmentioning
confidence: 99%
“…Most of these studies have focused on the interaction between surface acoustic waves propagating at the interface between a (piezoelectric) substrate and a thin magnetostrictive film with macroscopic dimensions [5,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In addition, also numerical and theoretical studies on magnetoelastic plane waves in bulk media have been reported [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%